Hormonal Profile and Fertility Response to Modified Ovsynch Protocol in Repeat Breeding Crossbred Cows with Prolonged Estrus - Patel, Dhaval N.; Nakhashi, Haresh C.; Chauhan, Prakash M.; Sutaria, Tarun V.; Chaudhari, Ashwin I.; Chaudhari, Ravji K.; Suthar, Babulal N. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The present study was conducted to determine the hormonal profile and fertility response in prolonged estrus affected repeat breeder  crossbred cows by using modified ovsynch protocol. Total 20 crossbred cows, not conceiving even after more than four services were  selected from the semi-arid area of Banaskantha district in Gujarat. They were divided into two equal groups: Group-I (n=10) - cows  with prolonged estrus period (>28 hrs) and Group-II (n = 10) - cows with normal estrus period (18 to 28 hrs). The animals of both groups  were treated with modified ovsynch protocol using double dose of GnRH (@ 20 μg) starting from 5th day of estrous cycle. The blood  was collected on day 0, 7th, 9th and 25th (15th day post-FTAI) of the treatment for determination of plasma progesterone and estradiol  hormones. The conception rates in group I and II were 60 and 70%, respectively. The cows with prolonged estrus had non-significantly  higher mean plasma progesterone (3.51 ± 0.45 vs 2.97 ± 0.38 ng/ml) and lower estradiol (44.36 ± 1.74 vs 54.56 ± 2.49 pg/ml) as compared  to normal estrus cows on day 0 of protocol. The progesterone levels were significantly (p
Keywords: Crossbred cow; Prolonged estrus; Modified ovsynch; Fertility; Progesterone; Estradiol